SQL practical guide for developers - Donahoo, Michael J.; Speegle, Gregory D. (Gregory David) (Amsterdam ; Boston : Elsevier, 2005)
Would the basics of SQL querying be useful to you, but you dont want to start at the very beginning? Do you wish you had an easy way to ramp up quickly to get a basic understanding of key features and capability? Then you need this book! Without a ton of conceptual information or general programming basics you already know, this book is a quick guide for computing professionals and programmers to learn the basics--and more--in an easily digestible way. + Provides tutorial-based instruction for the main features of SQL for programmers and other technical professionals in need of a brief but really good introduction to SQL. + The approach is vendor-neutralso very adaptable and flexiblebut the book's Web site includes information about DBMS-specific peculiarities. + The focus is on teaching concepts by walking through concrete examples and explanations, and self-review exercises are included at the end of each chapter. + Coverage is on the key features of the language that are required to understand SQL and begin using it effectively. + SQL 2003-compliant.
Databasics -- Retrieval : basic SELECTion -- Reshaping results -- Aggregating results -- Joins -- Set queries : UNION, INTERSECT, and EXCEPT -- Subqueries -- Modifying data -- Creating, deleting, and altering tables -- Views -- Transactions -- Database privileges -- Introduction to cursors, embedded SQL, stored procedures, and triggers.
Includes index.
Keywords: SQL (Computer program language).; Electronic books